Formation of Positive Attitude Methods in Primary Class Students - Mamajonova Shokhista Kamoldinovna; Mamaziyayeva Charoskhan Mirzamirovna (Genius Journals, 2022)
An important stage in the student's educational activity is the stage of primary education. It is the task of every pedagogue and psychologist to form positive relationships, high positive and human characteristics in the student of this period. Therefore, a number of recommendations for the implementation of this urgent task are presented in this article
Keywords: Positive relationship; personality; characteristic; teacher